Studi Eksperimen Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Matematika Siswa Materi Barisan dan Deret Kelas XI (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2023)
One of the learning models that can be used to involve students in solving a problem is a problem based learning model that can be a bridge in the learning process of mathematics. The purpose of this study is to determine whether there is an effect of the problem based learning model on the mathematics learning outcomes of the material of sequences and series in class XI of SMA Negeri 5 Prabumulih. The population in this study were all students of class XI SMA Negeri 5 Prabumulih with a sample of class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. Based on the calculation of student learning outcomes using the problem based learning model, totaling 36 students, the average value = 75,00 and the standard deviation value is = 12,479 and student learning outcomes without using the problem based learning model are 33. students, obtained an average value of  = 53,94 and the standard deviation is = 13,565. After the data were analyzed, the values of tcount = 6.718 and ttable = 1.998 were obtained. This means that t count is in the rejection area of H0, meaning H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an effect of the problem based learning model on the mathematics learning outcomes of the material of sequences and series in class XI of SMA Negeri 5 Prabumulih, the truth is accepted.